(6-i)+(7+3i)=

Simple and best practice solution for (6-i)+(7+3i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6-i)+(7+3i)= equation:


Simplifying
(6 + -1i) + (7 + 3i) = 0

Remove parenthesis around (6 + -1i)
6 + -1i + (7 + 3i) = 0

Remove parenthesis around (7 + 3i)
6 + -1i + 7 + 3i = 0

Reorder the terms:
6 + 7 + -1i + 3i = 0

Combine like terms: 6 + 7 = 13
13 + -1i + 3i = 0

Combine like terms: -1i + 3i = 2i
13 + 2i = 0

Solving
13 + 2i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 2i = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 2i = 0 + -13
2i = 0 + -13

Combine like terms: 0 + -13 = -13
2i = -13

Divide each side by '2'.
i = -6.5

Simplifying
i = -6.5

See similar equations:

| -2(w+9)=4w-24 | | 21y+4-6y=9 | | 24=-12x^2+36x | | 1/(x^2-8)-1/(x^2-2x-2)=0 | | onethird(6x+24)-15=-onehalf(12x-6) | | ((((cos)x)-2)/(cos(x/2)))=2 | | 3x-15(3-4x)=-33+4(-2-1) | | 12(2/3-2w) | | 9u-43=-8(u-1) | | 7.5g+3.5g= | | x^2-8-x^2-2x-2=0 | | W/3–6=—8 | | 3x-15(3-4x)=-33+4(-2-2) | | 10x-4=x+5 | | x=22.665x+5428.92 | | 5.28=x+2.14 | | x^3+3x^2-2x+5=4x+13 | | 2/5(3x-7) | | 3.5n=-63 | | 22+(-8)-32-(-12)+8= | | 5x-2+1=9 | | 0+3*y=1 | | -6x^6-5x^5-31x^4-25x^3-29x^2-20x-4=0 | | a(a-4)-2ab+5b= | | 3(c+2)+6(c-6)= | | 28=-7h | | -8-y+8x+5y= | | 4n-8-n=9n+7 | | 8v+6(v-5)=26 | | 10x+9=3x+30 | | 2x^2+3x^3+5=4x^2-1 | | 6x+7y=250 |

Equations solver categories